Digestive Transit Restoration After Esophagectomy - Praderi, Luis A; Balboa, Oscar; Bergalli, Luis; Blasiak, José; Delgado, Bolívar; Lira, Exequiel; Morelli, Raúl; Netto, Juan (Cirugía del Uruguay, 1980)
Substitution of the esophagus by visceral plasties has reached a high technical leve!, thus opening the way for its generalized indication in the treatment of dysphagia.